Applications of management science. Vol. 15 - Lawrence, Kenneth D.; Kleinman, Gary (Emerald, 2012)
Applications of Management Science is a blind refereed series, published annually. It presents state-of-the-art studies in the application of management science to solve significant managerial decision-making problems. Volume 15 examines management science application to data envelopment analysis and efficiency, supply chain and quality applications, and multi-criteria and financial applications. Section A focuses on DEA to team performance, public higher education systems, US airlines and Indian commercial banks. Section B focuses on cooperative public service advertising, supply chain strategies, optimal management of reverse supply chain and optimal response to multi-response models. Section C explores multi-criteria measures of public and private enterprises, two-dimensional warranty policy decision making, and creating teams. Section D focuses on financial applications, direct foreign investments, conditional values of risk in portfolio models, and asset allocations of mutual funds. This volume will be most valuable to practitioners and researchers interested in productivity analysis, supply chain systems, multi-criteria applications and financial applications.
Keywords: Business logistics -- Decision making.; Multiple criteria decision making.; Business enterprises -- Finance -- Decision making.; Data envelopment analysis.; elektronické knihy; electronic books